Early predictors of 28-day mortality in children with septic shock: Results from a prospective cohort study - Nguyen, Phuong Minh; Tran, Ly Cong; Le, Duy-Truong Khac; Nguyen, Viet Trieu (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Septic shock is a leading cause of mortality in children, particularly in Vietnam. Limited intensive care resources in low- and middle-income countries make it crucial to identify predictors of 28-day mortality to optimize patient outcomes. This study aimed to identify factors associated with 28-day mortality in pediatric patients with septic shock. Methods: A prospective cohort study was conducted on pediatric patients aged 2 months to 15 years who were diagnosed with septic shock in the Pediatric Intensive Care Unit of a tertiary pediatric hospital in southern Vietnam between July 2022 and June 2024. Results: Clinical and laboratory manifestations of septic shock at diagnosis varied widely among patients. The cumulative 28-day mortality rate was 64.1% (95% CI: 45.7–76.2%), with most fatal outcomes (53.8%; 95% CI: 35.6–66.8%) occurring within the first week. Although infants and male patients had the highest incidence rates of septic shock, these demographic factors were not significantly associated with mortality. Neurological, renal, and hematological dysfunctions, along with a lactate-to-albumin ratio (LAR) ≥ 1.84, were identified as independent predictors of 28-day mortality. A LAR ≥ 1.84 was associated with a 7.14-fold increase in mortality risk (95% CI: 2.56–24.9, p < 0.001). Conclusions: Pediatric septic shock is associated with a high 28-day mortality rate and diverse clinical presentations. Neurological, renal, and hematological dysfunctions, as well as a lactate-to-albumin ratio ≥ 1.84, were identified as independent prognostic factors for mortality, underscoring the need for focused management of these risk factors.